Features of the Physical Development of Children with Bronchopulmonary Dysplasia - G.S. Senatorova; O.L. Logvinova (Zaslavsky O.Yu., 2013)
We observed 131 children (269 cases) with a diagnosis of bronchopulmonary dysplasia. It is found that children with bronchopulmonary dysplasia are characterized by a delay in weight gain (73.9 ± 2.8 %, p < 0.0001), height (54.8 ± 3.2 %, p < 0.001) and body mass index (67.50 ± 3.03 %, p < 0.001). In 50 % of female patients body mass indices reached a standard in 36 months of corrected age, growth - in 24 months. Among male patients in 36 months corrected age, 25 % subjects had average weight and 50 % - the standard median growth. In children with bronchopulmonary dysplasia moderate correlation of weight gain with respiratory failure stage II (r = -0.442, p < 0.05) and a significant one - the symptoms of respiratory distress degree III (r = -0.676, p < 0.05) has been revealed. The dynamics of growth was significantly less correlated with signs of respiratory failure II and III degree than body weight (p < 0.05). The high sensitivity of the dynamics of body weight to the presence of episodes of hypoxia and impaired neurorespiratory drive (p < 0.05).